Optic nerve glioma - U. Masilionytė; E. Zarambaitė; B. Glebauskienė; A. Radžiūnas (Neurologijos seminarai)
Optic nerve glioma (ONG) is usually a low-grade tumor of the optic nerve. ONG can affect not only the optic nerve, but also the optic nerve chiasma and optic nerve tract. ONG can be classified as associated with neurofibromatosis type 1 (NF1) or sporadic ONG. Sporadic gliomas are more commonly diagnosed in adults, have an aggressive course, and are known to have a poor outcome. The disease can be asymptomatic. ONG often causes visual disturbances such as reduced visual acuity, visual field defects, and impaired color vision; due to the tumor mass effect, proptosis, strabismus, and diplopia are possible. As the disease progresses, various neurological symptoms can appear, including headache, hemiplegia, and endocrine disorders such as early maturation, growth hormone hypersecretion, or deficiency. A presumed diagnosis is based on clinical presentation and neuroimaging findings. Meanwhile, biopsy should be avoided due to the high probability of optic nerve damage. Treatment is individual for each patient, but remains controversial to this day. Thus, in this article, we review the prevalence, clinic, diagnostic and treatment options of ONG.